MOLECULAR DOCKING STUDY OF EPIGALLOCATECHIN GALLATE ON FLT3 IN COMPLEX WITH GILTERITINIB FOR ANTICANCER ACTIVITY - KURIAN, THOMAS (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of the study was to predict the binding affinity and interaction patterns between EGCG and FLT3 in complex with gilteritinib using molecular docking simulations. stabilization of the EGCG-FLT3-gilteritinib complex. Methods: The crystal structure of FLT3 in complex with gilteritinib was downloaded from the Protein Data Bank (PDB) database. Epigallocatechin gallate (EGCG) was obtained from the PubChem database. Auto Dock 8 software was utilized for the molecular docking study. The docking results are analyzed to identify the best pose based on binding affinity, hydrogen bonding, and other favorable interactions. The Discovery Studio Visualizer or other suitable software was used to visualize the protein-ligand interactions and analyze the binding mode of EGCG within the FLT3-gilteritinib complex. Results: The best ranking for ligands binding was at run 7 with the estimated free energy of binding −7.87 kcal/mol the estimated inhibition constant (ki) was 1.69 μm. The final intermolecular energy was −11.45 kcal/mol. kcal/mol It had 12 active torsions. The redocking score using gilteritinib was used as a control for the validation of the study. The estimated free energy of binding was −7.91 kcal/mol. The estimated inhibition constant ki is 1.60 μm. It had nine active torsions. Conclusion: Comparing the various binding energies and torsions of the test compound and the control revealed that the test epigallocatechin had a perfect docking score, and it was predicted to possess comparable anti-tumor and anticancer activity.